Population-based matching comparison between radiofrequency ablation and percutaneous ethanol or acetic acid injection for hepatocellular carcinoma. Issue 9 (September 2020) - Chang, Yun-Jau; Chen, Li-Ju; Chang, Yao-Jen; Chen, Po-Da
Abstract: Background: Loco-regional therapies are evolving for hepatocellular carcinoma (HCC) treatment. Radiofrequency ablation (RFA) has changed the landscape in treating HCC; however, percutaneous ethanol or acetic acid injection (PEI/PAI) remains a widely used and easily performed technique by experienced clinicians. Nevertheless, the effectiveness of RFA compared to that of PEI/PAI remains unclear. Methods: Records of 73, 136 patients with newly diagnosed HCC between 2007 and 2013 were drawn from the Taiwan Cancer Registry. The primary outcome measures were the overall survival and local recurrence-free survival. Propensity score matching (PSM) was performed to compare the effectiveness of RFA and PEI. Median follow-up time was 61.6 months (36–120 months). Results: After PSM, 4496 patients diagnosed with stage I-III HCC, who were initially treated with RFA (3372 patients) or PEI/PAI (1124 patients), were assessed. Compared to PEI/PAI, patients treated with RFA had better 5- and 9-year overall survival, cancer-specific survival, disease-free survival, and local recurrence-free survival. Median overall survival and recurrence-free survival of patients treated with RFA vs PEI/PAI were 61.5 vs 41.9 months and 72.1 vs 45.2 months, respectively. Multivariate Cox model analysis revealed that, except for patients with high cell grade or advanced stage, RFA resulted in better overall survival (HR: 0.74, 95% CI 0.68–0.81, P < 0.001) and local recurrence-free survival (HR: 0.69, 95% CI 0.63–0.75, P < 0.001) than PEI/PAI. Conclusions: RFA provides advantages over conventional PEI/PAI for HCC. Considering technological advances in instruments, loco-regional therapies for HCC can be employed in carefully selected patients.